Simulation levels in teaching power electronics - Darwish, Mohamed; Marouchos, Christos (My University, 2014)
There are several simulation packages which can be used in teaching power electronics. Many of these packages have the ability to simulate power electronic circuits at different levels of depth. Sometimes the students are not sure how accurate do they need to simulate their circuits. Do they need to use ideal switches in their simulation? Do they need to use the exact model of the switches used in practical circuits? Or can they use something in between? Is the level of the simulation related to the level of teaching? The main aim of the simulation in designing power electronic circuits may be obvious; however is the aim of using simulation in teaching power electronics clear? Is the aim just to teach students how to use simulation packages or is it more than that? In this paper the authors will try to answer the above questions. With more than 50 years of experience in teaching power electronics at different levels between them the authors present a critical vision of how power electronics simulation can be taught at different levels and what are the requirements of the simulations at these levels.
Keywords: Education in Power Electronics; OrCAD; Power Electronics; PSPICE Simulation; Simulation in Power Electronics